Fast Development of Self-Assembled, Highly Oriented Polymer Thin Film and Observation of Dual Sensing Behavior of Thin Film Transistor for Ammonia Vapor - Sahu P.K.; Chandra L.; Pandey R.K.; Mehta N.S.; Dwivedi R.; Mishra V.N.; Prakash R. (My University, 2025)
The technological demand for polymer thin film transistors (PTFTs) is continuously increasing because of their potential applications in various kinds of sensor designs. Despite this, there is need for development of a facile technique that can produce high performance low cost PTFTs. Therefore, a facile method is presented for ultrafast formation of large area self-assembled, highly orientated, crystalline polymer thin films at high surface free energy mobile air–liquid interface named “floated polymer thin film over fluid substrate.” The grown thin film over different solid substrates is studied by multiple-characterization techniques viz. high resolution-transmission electron microscopy, grazing incident X-ray diffraction, absorption spectroscopy, and cyclic voltammetry. Finally, the PTFTs having bottom gate and top contact configuration with the variations in source-drain (S/D) electrode is fabricated for ammonia sensing. A synergistic enhanced ammonia vapor sensing performance with dual sensing characteristics through Pd-electrode based PTFTs is observed when it is operated in two different modes of operation, that is, ON state to OFF state and vice-versa. However, this transition is absent in Au-electrode based PTFTs. Further, the observation of high gas response and dual sensing phenomena for ammonia vapor is argued by the evidence from a higher (approximately threefold) mobility, scanning electron microscopy (SEM), and atomic force microscopy (AFM) images. © 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim